2008
DOI: 10.1016/j.toxlet.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical assessment of deoxynivalenol tissue distribution following oral exposure in the mouse

Abstract: Deoxynivalenol (DON or vomitoxin) is a trichothecene mycotoxin commonly found in cereal grains that adversely affects growth and immune function in experimental animals. A competitive enzyme-linked immunosorbent assay (ELISA) was used to monitor the kinetics of distribution and clearance of DON in tissues of young adult B6C3F1 male mice that were orally administered 25mg/kg bw of the toxin. DON was detectable from 5 min to 24h in plasma, liver, spleen and brain and from 5 min to 8h in heart and kidney. The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 38 publications
4
68
1
1
Order By: Relevance
“…Importantly, some of these alterations, including glutamate uptake, microglial viability, and modulation of the neuroinflammation, are observed at very low doses of toxin (50-200 nM). Pestka et al (2008b) have elegantly shown in mice that after oral exposure the amount of DON able to cross the blood-brain barrier corresponds approximately to 10% of its blood concentration. Based on that study and on the actual provisional maximum tolerable daily intake (PMTDI) of DON fixed at 1 lg/kg of body weight that gives a maximum blood concentration of 14 lg/L or 47 nM, it could be extrapolated that the brain concentration of DON could reach 4.7 nM in human exposed to DON at its PMTDI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, some of these alterations, including glutamate uptake, microglial viability, and modulation of the neuroinflammation, are observed at very low doses of toxin (50-200 nM). Pestka et al (2008b) have elegantly shown in mice that after oral exposure the amount of DON able to cross the blood-brain barrier corresponds approximately to 10% of its blood concentration. Based on that study and on the actual provisional maximum tolerable daily intake (PMTDI) of DON fixed at 1 lg/kg of body weight that gives a maximum blood concentration of 14 lg/L or 47 nM, it could be extrapolated that the brain concentration of DON could reach 4.7 nM in human exposed to DON at its PMTDI.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that satratoxins possess direct neurotoxic effects, resulting in neuronal cell death and neuroinflammation (Corps et al, 2010;Pestka et al, 2008a). Although studies have demonstrated that trichothecenes, including DON, could cross the blood-brain barrier, accumulate in the brain and cause neurologic disorders (Pestka et al, 2008b;Ravindran et al, 2011), no evaluations of their effect on astrocytes or microglia have been conducted. In the present study, we investigated the effect of the ribotoxin DON on the viability and functions of astrocytic and microglial cells of animal and human origin.…”
Section: Introductionmentioning
confidence: 99%
“…Other mycotoxins detected were zearalenone and AFT B1. In other work ELISA was used to monitor the kinetics of distribution and clearance of DON in tissues of young adult B6C3F1 male mice that were orally administered with toxin [180]. DON was detectable from 5 min to 24 h in plasma, liver, spleen and brain and from 5 min to 8 h in heart and kidney.…”
Section: Other Methodsmentioning
confidence: 99%
“…Notably, there is a strong inverse relationship between food consumption and brain levels of serotonin (5-hydroxytryptamine, 5-HT), an important upstream regulator of aforementioned peptides [7]. Since DON is detectable in brain following oral administration [8], the toxin has the potential to interfere with normal appetite regulation. In support of this contention, exposure to DON at 2.5 mg/kg - bw significantly increases serotonin levels in cerebellum and hypothalamus in rats at 24 hr after administration [9, 10].…”
Section: Introductionmentioning
confidence: 99%